Principles of environmental management : the greening of business - Buchholz, Rogene A. (Upper Saddle River, New Jersey : Prentice Hall, 1998)
Environment Management
Keywords: Environmental management; Business; Environmental policy; Industrial management; Social responsibility; Ecology; Environmental ethics; Environmental problems